2020
DOI: 10.1039/d0cy00784f
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol-to-butadiene: the reaction and its catalysts

Abstract: Catalytic conversion of ethanol is a promising technology for producing sustainable butadiene. This paper reviews the reaction and its catalysts, and discusses the challenges their development faces.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
107
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(128 citation statements)
references
References 252 publications
(863 reference statements)
4
107
0
Order By: Relevance
“…Nevertheless, acid-base pair concept should not be confused with the coexistence on a same material of acidic and basic phases. For example, in the case of MgO-SiO2 system that was extensively studied for bio-ethanol cascade reaction conversion into butadiene and recently reviewed by Pomalaza et al [175], it was shown that acidic sites (on silica or on magnesium silicates) are involved in the dehydration steps whereas the basic ones (on MgO) catalyse the dehydrogenation and condensation steps. In this case, the catalyst is bifunctional, the two properties are independently characterized and the optimal balance between acid and base phases is defined.…”
Section: Acid-base Pairs and Their Characterizationmentioning
confidence: 99%
“…Nevertheless, acid-base pair concept should not be confused with the coexistence on a same material of acidic and basic phases. For example, in the case of MgO-SiO2 system that was extensively studied for bio-ethanol cascade reaction conversion into butadiene and recently reviewed by Pomalaza et al [175], it was shown that acidic sites (on silica or on magnesium silicates) are involved in the dehydration steps whereas the basic ones (on MgO) catalyse the dehydrogenation and condensation steps. In this case, the catalyst is bifunctional, the two properties are independently characterized and the optimal balance between acid and base phases is defined.…”
Section: Acid-base Pairs and Their Characterizationmentioning
confidence: 99%
“…Reducing the ethanol partial pressure appeared to increase the selectivity, which has been observed previously. 9 Da Ros et al 31 obtained a butadiene yield of around 20 % at 723 K on 95:5 MgO-SiO 2 and Taifan et al 26 reported up to 30 % selectivity for butadiene under similar conditions, but with significantly more ethylene formation.…”
Section: Microkinetic Analysismentioning
confidence: 96%
“…of sugars, [27,90] wood pyrolysis with addition of calcium carbonate [65] S HO OH OH glycerol byproduct of biodiesel production (50 wt%) [91][92] S OH Me Me O acetoin fmt. of sugars (>40 g/L) [93] P 1,3-butadiene (grain or potato) catalytic gas phase synthesis from ethanol [94] S Me HO 1-butanol ABE-fmt. of sugars (34 wt%) [27,74]…”
Section: P Me Mementioning
confidence: 99%